En diktat om dansk litteraturhistorie - Conrad, Flemming (Danske Studier, 2024)
This article focuses on a manuscript of about 600 pages containing a complete history of Danish literature including medieval Norse literature and Norwegian literature since 1814. It is taken down by a training college student at the Hjørring college of education from the dictation of his teacher during the educational year 1914-15. It gives us an exceptional idea of how literary history was taught and how a code of morality was laid down in this subject.